Study of Some Physico-chemical Parameters and Their Effect on Potential Fish Yield in Gbedikere Lake, Bassa, Kogi State, Nigeria - Adeyemi, S.O. (Pakistan Journal of Nutrition, 2011)
The study of physico-chemical parameters and their effect on potential fish yield in Gbedikere Lake was carried out. Water samples were collected between 9 am and 10 am every fourth nightly from three sampling points marked A, B and C between September 2006 and December 2008. Temperature and Transparency were measured on the field using Temperature Meter (9091 model) and Secchi-disk. 250 ml of water samples were collected and transported to the Biological Sciences Laboratory for analysis of pH, Dissolved Oxygen (DO2), Conductivity and Total Dissolved Solids (TDS). The result showed that Temperature, pH, Conductivity, DO2, TDS and Transparency ranged from 26-29oC, 5.08-8.02, 0.04-42.19 ms/m2/mol-1, 6.1-19.85 mg/l, 13.00-45.00 mg/l and 8.0-68.7 cm respectively. The correlation matrix for physico-chemical parameters revealed that there was no significant difference between Temperature, pH and Conductivity (p<0.05) with a significant difference (p>0.05) between Temperature, TDS, pH and Conductivity in the three sampling points. Water quality parameters of the lake were found to be suitable for fish production.